PENGARUH INVESTASI, PENGELUARAN PEMERINTAH DAN TENAGA KERJA TERHADAP PERTUMBUHAN EKONOMI DI KABUPATEN MUSI RAWAS - Subianto, Subianto (MOTIVASI, 2016)
Purpose - The purpose of this research was to analyze the Influence between economic growth in MusiRawas with the Investment, Government Expenditure and Employment Musi Rawas. Design/methodology - The data used in this research is secondary data in the form of time series data from 1994 till 2013. The analytical tool used to determine the effect of independent variables with dependent variable is by using multiple regression analysis.Findings â€“ The author finds that the independent variables were used as models in this study could explain the dependent variable and the remaining 59,07% isÂ  explained by other variables that are not included in this study. Based on the results of F-test that overall the independent variable (Investment, Government Expenditure and Employment) provides a significant influence on the dependent variable (Growth). While partially based regression test revealed that only Labour that do not significantly affect economic growth, while investment and government spending affect the economic growth